Isoperimetric surfaces and area-angular momentum inequality in a rotating black hole in new massive gravity - Aceña, Andrés Esteban (2018)
We study the existence and stability of isoperimetric surfaces in a family of rotating black holes in new massive gravity. We show that the stability of such surfaces is determined by the sign of the hair parameter. We use the isoperimetric surfaces to find a geometric inequality between the area and the angular momentum of the black hole, conjecturing geometric inequalities for more general black holes.